Impact of chromium substitution on structural and magnetic properties of MnBi-based melt-spun ribbons - VUONG, Anh Kha; DANG, Triet Minh; NGUYEN, Truong Xuan; NGUYEN, Duy Anh Vo; PHAM, Hai Van; NGUYEN, Nam Hoai; PHAM, Nam Hong; VUONG, Oanh Kim Thi; LE, Tan Nhut Nguyen; DINH, Tuan Van; NGUYEN, Nam Thanh Tran; TRAN, Nhan Thi; et al. (Journal of Metals, Materials and Minerals, 2026)
MnBi-based magnetic materials and magnets are of significant interest due to their magnetism without rare earth elements and their ability to replace Nd-Fe-B in high-temperature magnet applications due to its unique feature of enhancing coercivity in the range of 100℃ to 250℃, enabling their energy product (BH)max comparable to NdFeB magnets despite their moderate spontaneous magnetization Msp. To adjust the magnetic properties of MnBi magnets, various elements have been doped to regulate magnetic interactions among the atoms, which subsequently alters Msp and the magneto-crystalline anisotropy energy. In this work, we investigate the effects of chromium doping on the magnetic properties of MnBi. The investigation includes the highlights of density functional theory (DFT) calculations and the results of doping experiments to elucidate the role of Cr dopant. The DFT consideration reveals the dynamic stability of Cr-doped MnBi system, the preferential substitution of Cr for Mn leading to the complicated modifications in the local magnetic environment. The experimental results shown the incorporation of Cr atoms into MnBi lattice and refine the microstructure of the melt-spun ribbons. Currently, the best magnetic properties are due to the Mn52.5Cr2.5Bi45 annealed at 300℃ for 3 h with the content of the ferromagnetic phase LTP of 65.8 wt%, the saturation magnetization measured at 30 kOe Msat = 54.6 emu∙g‒1, the coercivity iHc = 4.2 kOe but the energy product (BH)max is only 3.64 MGOe.